Epidemiology of sleeping disorders among doctors during COVID-19 pandemic in Pakistan - Alishba Malik, Muhammad Arif, Naureen Ahmed Syed, Muhammad Kashif Bashir, Nasir Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Novel coronavirus disease or COVID-19, an acute respiratory illness caused by a newly discovered SARS-CoV-2 virus emerged in December 2019. Objectives: The main objective of the study is to find the epidemiology of sleeping disorders among doctors during COVID-19 pandemic in Pakistan. Material and methods: This cross sectional study was conducted in Sir Ganga Ram Hospital Lahore during June 2021 to December 2021. A questionnaire was used to collect the data. Among the topics covered in the survey were questions regarding the quality of one’s night’s sleep, where one keeps infection control supplies, how one copes with stress and depression, how one learns about COVID-19 on the internet, how one views risk, and other personal information. The survey was completed over the internet. Results: The data was collected from 200 patients. Over half (55.0 percent) were married and under the age of 35. (49.1%). The majority of respondents (57.8%) spend more than two hours a day on social media. The great majority of them came from the upper echelons of the workforce. There were 38.3%, 29.8%, and 29.1%, respectively, of those who reported a worse sleep quality following the onset of COVID-19, according to their weighted proportions. Conclusion: It is concluded that COVID-19 is widely spreading in Pakistani doctors. Mental health disorders and poor sleep quality are more widespread in the medical field because of the heightened danger of exposure during pandemic illnesses.